Analisis Metode Forecasting Terhadap Open Po Dan Actual Delivery Customer Pada PT. Arsi. - Mustofa . (Journal Of Communication Education, 2019)
ABSTRACTThis study aims to determine the method of precise forecasting of the existence of deviations that occur between open PO and actual delivery. Theory and theoretical framework used are open PO and actual delivery. This research data is quantitative data and data obtained that is secondary data. The research design use survey method, data collection technique that is observation. Data analysis method using forecasting moving average method and forecasting exponential smoothing method. Based on the objectives and the formulation of the problems studied, this research includes descriptive research aimed to know the phenomenon that occurs between open PO to actual delivery. The results showed that from three stages of testing obtained method of moving average chosen as the best method with MAD, MSE, and MAPE 90,587, 13,896,662,502 and 0.71% . The deviation of the decline from 107,181 to 90,587 in the percentage decrease of 15.48%. With the accuracy of the use of the correct forecasting method, the stability of the stock finish and good stock of materials will be more stable, with the condition the company can do business activities calmly, delivery is always on time and customers increasingly put a high trust to the company so that the relationship and cooperation is very good and strong.Keywords: Open PO, Actual Delivery, Forecasting Method Moving Average, Exponential Smoothing Forecasting Method. ABSTRAKPenelitian ini bertujuan untuk mengetahui metode forecasting tepat atas adanya penyimpangan yang terjadi antara open PO dan aktual delivery. Teori dan kerangka pikir teori yang digunakan yaitu open PO dan aktual delivery. Data penelitian ini merupakan data kuantitatif dan data yang diperoleh yaitu data sekunder. Desain penelitian menggunakan metode survei, tehnik pengumpulan data yaitu observasi. Metode analisa data dengan menggunakan metode forecasting moving average dan metode forecasting exponential smoothing. Berdasarkan tujuan dan perumusan masalah yang diteliti, penelitian ini termasuk penelitian deskriptif bertujuan untuk mengetahui fenomena yang terjadi antara open PO terhadap aktual delivery. Hasil penelitian menunjukkan bahwa dari tiga tahap pengujian diperoleh metode moving average terpilih sebagai metode terbaik dengan nilai MAD,MSE dan MAPE, 90.587, 13.896.662.502 dan 0.71%. Penyimpangan terjadi penurunan dari 107.181 menjadi 90.587 secara persentase penurunan yang terjadi sebesar 15,48%. Dengan ketepatan penggunaan metode forecasting yang benar maka kestabilan stok finish good dan stok material akan lebih stabil, dengan kondisi tersebut perusahaan bisa melakukan kegiatan bisnis dengan tenang, delivery selalu on time dan pelanggan semakin menaruh kepercayaan yang tinggi kepada perusahaan sehingga hubungan dan kerjasama terjalin sangat baik dan kuat.Kata kunci: Open PO, Aktual Delivery, Metode forecasting Moving Average, Metode Forecasting Exponential Smoothing.